DEVELOPMENT OF CANE SUGAR (SACCHARUM OFFICINARUM) PRODUCTION WITH THE PRODUCTION FACTOR APPROACH IN BELANG MANCUNG VILLAGE, KETOL DISTRICT, ACEH CENTRAL REGENCY - Gustina Siregar; Yudha Andriansyah Putra; Dewa Putu Siantara; Indah Indriyani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
The goal of this study was to see how much production parameters influenced sugarcane farming in Belang Mancung Village, Ketol District, Central Aceh Regency. The second goal is to determine whether or not the employment of production variables in sugarcane cultivation in Belang Mancung Village, Ketol District, Central Aceh Regency, is effective. The Cobbdouglass analysis method and the price efficiency approach were employed in this study's data analysis. The results of this study show that the computed F is more than the F table (1042,423 > 2,74) with the choice criterion to accept H1 and reject H0 simultaneously, based on regression analysis based on the F test.